Pain perception toward orthodontic treatment - Eka Erwansyah; Fajriani; Anisah Nabilah Ferry (Makassar Dental Journal PDGI Makassar, 2020)
Background: Pain is defined as an unpleasant sensory and emotional experience associated with tissue damage. In orthodontic treatment, pain and discomfort are two common conditions experienced by most orthodontic patients during the treatment procedure. The emergence of this pain will have a major influence on the success of orthodontic treatment, given that the pain can reduce patient motivation in continuing treatment. Objective: to review the effect of orthodontic device movements on the pain caused and the factors that influence it. Method: Scientific evidence and clinical cases were drawn from the literature to support this review and information about pain perception during orthodontic treatment. Conclusion: The pain caused during orthodontic treatment is considered a normal condition because it is a biological event that is interrelated between the force exerted, local inflammation, the mechanism of action of orthodontic equipment on the teeth.